Philosophy of interdisciplinarity - Schmidt, Jan C. (Jan Cornelius), 1969- author.
1 online resource.
Keywords: "Interdisciplinarity is a hallmark of contemporary knowledge production. This book introduces a Philosophy of Interdisciplinarity at the intersection of science, society, and sustainability. In light of the ambivalence of the technosciences and the challenge of sustainable development in the Anthropocene, this engaged philosophy provides a novel critical perspective on interdisciplinarity in science policy and research practice. It draws upon the original spirit of interdisciplinarity as an environmentalist concept and advocates an essential change in human-nature relations. The author utilizes the rich tradition of philosophy for case study analysis and develops a framework to disentangle the various forms of inter- and transdisciplinarity. Philosophy of Interdisciplinarity offers a foundation for a critical-reflexive program of interdisciplinarity conducive to a sustainable future for our knowledge society and contributes to fields such as sustainable sciences, social ecology, environmental ethics, technology assessment, complex systems, philosophy of nature, and philosophy of science. It injects a fresh way of thinking on interdisciplinarity - and supports researchers as well as science policy makers, university managers, and academic administrators in critical-reflexive knowledge production for sustainable development"--